Periodicals Use Pattern by Teachers and Research Scholars of Kuvempu University: A Case Study - Biradar, B. S.; Sampath Kumar, B. T. (Journal of Information and Knowledge, 2000)
Study attempted to identify the periodicals use pattern by Teachers and Research Scholars in an University environment. Authors have tried to trace out the impact of personal attributes on use of periodicals.